Globalization and the Inequality of Nations. - Krugman, P; Venables, A (National Bureau of Economic Research, 1995)
A monopolistically competitive manufacturing sector produces goods used for final consumption and as intermediates. Intermediate usage creates cost and demand linkages between firms and a tendency for manufacturing agglomeration. How does globalization affect the location of manufacturing and gains from trade? At high transport costs all countries have some manufacturing, but when transport costs fall below a critical value a core-periphery pattern spontaneously forms, and nations that find themselves in the periphery suffer a decline in real income. At still lower transport costs there is convergence of real incomes, in which peripheral nations gain and core nations may lose.